USE OF NON-TRADITIONAL DIDACTIC METHODS IN THE SYSTEM TRAINING OF MEDICAL SPECIALISTS - NEED AND TRENDS - T. Biyanka (Academy of Cognitive and Natural Sciences, 2004)
The reform in the field of Health Care is connected with a reform in medical education and the forming of new types of medical specialists, who match the new aims of medicine, the new conditions of life, and the needs of the population. This calls for new kinds of forms and methods of medical education.